Recurrent acute myocarditis: An under-recognized clinical entity associated with the later diagnosis of a genetic arrhythmogenic cardiomyopathy - Ollitrault, Pierre; Al Khoury, Mayane; Troadec, Yann; Calcagno, Yoann; Champ-Rigot, Laure; Ferchaud, Virginie; Pellissier, Arnaud; Legallois, Damien; Milliez, Paul; Labombarda, Fabien (Frontiers in Cardiovascular Medicine, 2022)
Background Myocardial inflammation has been consistently associated with genetic arrhythmogenic cardiomyopathy (ACM) and it has been hypothesized that episodes mimicking acute myocarditis (AM) could represent early inflammatory phases of the disease. Objective We evaluated the temporal association between recurrent acute myocarditis (RAM) episodes and the later diagnosis of a genetic ACM. Materials and methods Between January 2012 and December 2021, patients with RAM and no previous cardiomyopathy were included (Recurrent Acute Myocarditis Registry, NCT04589156). A follow-up visit including clinical evaluation, resting and stress electrocardiogram, cardiac magnetic resonance imaging, and genetic testing was carried out. Endpoints of the study was the incidence of both ACM diagnosis criteria and ACM genetic mutation at the end of follow-up. Results Twenty-one patients with RAM were included and follow-up was completed in 19/21 patients (90%). At the end of follow-up, 3.3 ± 2.9 years after the last AM episode, 14/21 (67%) patients with an ACM phenotype (biventricular: 10/14, 71%; left ventricular: 4/14, 29%) underwent genetic testing. A pathogenic or likely pathogenic mutation was found in 8/14 patients (57%), 5/8 in the Desmoplakin gene, 2/8 in the Plakophillin-2 gene, and 1/8 in the Titin gene. Family history of cardiomyopathy or early sudden cardiac death had a positive predictive value of 88% for the presence of an underlying genetic mutation in patients with RAM. Conclusion RAM is a rare entity associated with the latter diagnosis of an ACM genetic mutation in more than a third of the cases. In those patients, RAM episodes represent early inflammatory phases of the disease. Including RAM episodes in ACM diagnosis criteria might allow early diagnosis and potential therapeutic interventions.